Determination of Heavy Metals in the Different Samples of Table Salt - Muhammad Rizwan; Murtaza Haider; Abrar Ul Hassan; Sakhawat Ali (Journal of Basic & Applied Sciences, 2017)
Table salt is most widely used food additive around the globe. Any contamination to salt may lead to health hazards and ailments. In this study concentration of heavy metals were determined in different table salt sample. Twelve different salt sample were collected from various localities of Pakistan including all the four provinces. The concentration lead (Pb), Cadmium (Cd), Chromium (Cr), Iron (Fe), Manganese (Mn) and Copper (Cu) were determined by atomic absorption spectroscopy and compared it with Codex Alimentarius commission. The level of Pb, Cd, Cr, Fe, Mn and Cu were in the range of 0.1-2.96 mg/kg, 0.08-1.18 mg/kg,0.02-2.4 mg/kg, 2.5-16.7 mg/kg, 0.1-5.1 mg/kg, 0.6-3.1 mg/kg respectively. In most of the sample the level of toxic metal are within the permissible limits as prescribed by Codex Alimentarius Commission.